Trends and patterns of inequalities in using facility delivery among reproductive-age women in Bangladesh: a decomposition analysis of 2007–2017 Demographic and Health Survey data - Md Akhtarul Islam; Nusrat Jahan; Md Ashfikur Rahman; Satyajit Kundu; Sumaya Sultana; Harun Or Roshid; Zahidul Islam Khan; Mortuza Tohan; Bayezid Khan; Md Hasan Howlader (BMJ Open)
Objectives The prime objectives of the study were to measure the prevalence of facility delivery, assess socioeconomic inequalities and determine potential associated factors in the use of facility delivery in Bangladesh.DesignCross-sectional.Setting The study involved investigation of nationally representative secondary data from the Bangladesh Demographic and Health Survey between 2007 and 2017–2018.Participants The participants of this study were 30 940 (weighted) Bangladeshi women between the ages of 15 and 49.Methods Decomposition analysis and multivariable logistic regression were both used to analyse data to achieve the study objectives.Results The prevalence of using facility delivery in Bangladesh has increased from 14.48% in 2007 to 49.26% in 2017–2018. The concentration index for facility delivery utilisation was 0.308 with respect to household wealth status (p<0.001), indicating that use of facility delivery was more concentrated among the rich group of people. Decomposition analysis also indicated that wealth quintiles (18.31%), mothers’ education (8.78%), place of residence (7.75%), birth order (5.56%), partners’ education (4.30%) and antenatal care (ANC) seeking (8.51%) were the major contributors to the prorich socioeconomic inequalities in the use of facility delivery. This study found that women from urban areas, were overweight, had any level of education, from wealthier families, had ANC, and whose partners had any level of education and involved in business were more likely to have facility births compared with their respective counterparts.Conclusions This study found a prorich inequality in the use of facility delivery in Bangladesh. The socioeconomic disparities in facility delivery must be addressed if facility delivery usage is to increase in Bangladesh.